Jiternice and kolaches: food and identity in Wilson, Kansas - Miller, Jeffrey P., author; Safarik, Lynn, advisor; Albright, Leonard, committee member; Quick, Don, committee member; Smith, Kenneth, committee member (Colorado State University. Libraries, 2006)
This dissertation is a case study of the development and uses of personal and social identity in a small town (less than 1000 people) in north-central Kansas. Through the use of interviews, observation, document analysis, and analysis of material objects, it examines the tension between modernity and tradition as the town of Wilson, Kansas attempts to form an ethno-historical identity for both internal and external consumption. Wilson, Kansas is a town with a significant proportion of its population that is ethnically Czech. The town is attempting to use its primary ethnic background, Czech, and historical nature to deal with economic and demographic problems caused by its location away from major transportation infrastructures and lack of large-scale employers. This study discovered the ways in which the residents were using elements of Czech ethnicity and historical identity to create useful social and personal identities in the face of economic and demographic challenges created by their unique situation. The core of this dissertation focuses on the primary areas of the After-Harvest Czech Festival, the Midland Hotel, analysis of local cookbooks featuring Czech cooking, and changing meal patterns among local residents to examine the nature of the changing identity of the residents and the town. The four areas examined show the difference between the ways that ethnicity is performed in the public and private space and the way in which the Midland Hotel functions as a metaphor for the larger changes that are affecting the community. The amount of time I was able to spend in the field limited the number of directions I could take as well as the depth of analysis in these directions. Any of the areas of analysis in this dissertation could be expanded into full studies on their own. More research is needed on the role of the hotel in the community as this study concentrated more on the food. Comparative studies of Wilson and other communities with similar features could prove helpful as well.
Keywords: American studies; minority and ethnic groups; sociology; social structure; ethnic studies